Sporoderm microcapsule extraction & application - Potroz, Michael Graeme (2018)
The sporoderms of pollen and plant spores provide an ideal source of robust monodisperse capsules for microencapsulation applications. Plant-based sporoderms are nature’s solution to protecting sensitive genetic material from harsh environmental conditions and offer a promising natural solution to the large-scale manufacture of microcapsules. The outer sporoderm layer (exine) of pollen and spores typically comprises a biopolymer, sporopollenin, with remarkable physicochemical stability, and the inner sporoderm layer (intine) typically comprises a combination of common cellulosic materials. It is important to note that the sporopollenin and cellulosic layers comprising the sporoderm are free from allergenic compounds commonly associated with pollen. Through standard wet chemistry processing methods, allergenic proteins and other contaminants may be completely removed. There currently exist a wide range of chemical processing protocols for extracting sporopollenin sporoderm microcapsules (S-SMCs), as well as various techniques for the loading of compounds within S-SMCs. However, there is still a need for a systematic analysis of the efficacy of S-SMC extraction steps, and key factors influencing the loading and release of compounds within S-SMCs. Therefore, in this thesis, detailed studies were undertaken of the most commonly utilized S-SMC extraction protocol, the applicability of this protocol to genetically distant sources of S-SMCs was explored, and the dynamics of compound loading and release from S-SMCs were elucidated. Standard S-SMC extraction steps involve, defatting of surface lipidic compounds, base-hydrolysis of proteinaceous cytoplasmic contents, acid-hydrolysis of cellulosic materials, and washing for removal of processing residues, under varying experimental conditions. Through these studies, it was shown that base-hydrolysis is redundant and may actually damage the integrity of the sporoderm from some plant species. It is now clear that defatting and acid-hydrolysis alone are adequate to isolate S-SMCs. Acid-hydrolysis temperatures can be reduced from 170°C to 70°C, and processing times can be reduced from 7 days to 5 - 30 hours. Additionally, it was observed that excessive duration acidolysis, based on existing standard protocols, destabilizes the S-SMC microstructure and causes capsule fragmentation. With regards to mechanisms of S-SMC loading and release, it was identified that air bubble collapse drives S-SMC loading, and that methods of assisted loading are important to ensure the full loading of all S-SMC cavities. Through optimization of macromolecule loading it was possible to elucidate practical loading efficiencies and distributions, as well as to estimate theoretical maximum loading efficiencies. In vitro release studies resulted in both qualitative and quantitative analysis of release dynamics. Further studies with enteric coencapsulation allowed for the development of an S-SMC system for targeted intestinal delivery with tunable controlled release. Overall, these studies provide important insights into the ongoing exploration of these promising natural microcapsules and their potential for utilization in a wide range of industrial applications.